2019
DOI: 10.1590/0100-6991e-20192077
|View full text |Cite
|
Sign up to set email alerts
|

Fatores prognósticos de resposta à quimioterapia em tumores avançados do colo uterino: o papel da neoangiogênese.

Abstract: RESUMO Objetivo: analisar a expressão do Fator de Crescimento do Endotélio Vascular (VEGF), seu receptor (VEGFR-2), idade e tipo histológico de carcinomas avançados de colo uterino com relação à resposta clínica à quimioterapia neoadjuvante. Métodos: foram incluídas 40 pacientes com diagnóstico de carcinoma de colo uterino (IB2 e IVA), com biópsias prévias ao tratamento. Todas as pacientes foram submetidas à quimioterapia neoadjuvante e avaliadas quanto à resposta clínica e à expressão do VEGF. Considerou-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Out of total 36 cases, 16 cases (26.67%) were observed as a positive to VEGF and 20 cases (33.33%) showed negativity. It is similar to a study conducted by Kfouri et al [ 25 ] who noticed that 16 patients were positive for VEGF protein and 24 patients were considered negative due to low expression. However, other study reported higher rates of VEGF expression (66%), used previous published histoscore ≥200 for defining positivity of VEGF expression compared to our study [ 26 ].…”
Section: Discussionsupporting
confidence: 88%
“…Out of total 36 cases, 16 cases (26.67%) were observed as a positive to VEGF and 20 cases (33.33%) showed negativity. It is similar to a study conducted by Kfouri et al [ 25 ] who noticed that 16 patients were positive for VEGF protein and 24 patients were considered negative due to low expression. However, other study reported higher rates of VEGF expression (66%), used previous published histoscore ≥200 for defining positivity of VEGF expression compared to our study [ 26 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, the clinical features vary greatly among the populations studied, making it difficult to estimate the appropriate values. Additionally, numerous studies have explored whether abnormal expression of certain molecular markers is associated with tumor resistance to chemotherapy, such as VEGF, HIF-1a, EGFL7, and LDH [ 28 31 ]. These markers have been linked to hypoxia and angiogenesis in the tumor microenvironment and may be related to drug concentrations in neoangiogenesis regions.…”
Section: Discussionmentioning
confidence: 99%
“…New pharmacological options, including drugs oriented toward repairing damaged DNA, such as poly(ADP-ribose) polymerase inhibitors, antiangiogenesis medications, and immune checkpoint inhibitors, have been developed over the past years in order to improve the prognosis of women with advanced CC [84,85]. Several clinical trials are in progress, such as those that have been testing pembrolizumab, a programmed death inhibitor (PD-1) that was recently approved by the Food and Drug Administration to treat advanced or recurrent CC.…”
Section: Discussionmentioning
confidence: 99%